Analýza vztahu druhové bohatosti měkkýšů (Mollusca) a velikosti vzorkovací plochy na minerotrofních slatiništích - Černohorská, Nicole (2008)
The relationship between mollusc species richness and area was studied at 28 Western Carpathian treeless spring fen sites, differing in their mineral richness. In each site a set of three small nested quadrates of 25x25, 50x50 a 75x75 cm2 (the larger plot always containing the smaller plots) was sampled, from which mollusc data as well as vascular plant and bryophyte data were collected. Principal differences in the numbers of mollusc specimens and species were found when considering only live molluscs or empty shells as well. These differences were most marked at the more mineral-rich fen sites, where empty shells tend to accumulate over very long periods of time; at mineral-poor fen sites the empty shells dissolve relatively quickly due to low pH values. The number of species of each taxonomical group always increased with the increasing area. However, there were some differences in the species-area curves among the three taxonomical groups as well as among the three mineral types of.